The global burden of cardiovascular diseases and type 2 diabetes attributable to low physical activity, 1990–2019: an analysis from the global burden of disease study - Zhang, Junhan; Yuan, Zongxiang; Mo, Chuye; Kang, Yiwen; Wang, Fengyi; Wei, Xueqin; Huang, Shihui; Qin, Fang; Jiang, Junjun; Liang, Hao; Ye, Li (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiovascular diseases (CVD) and type 2 diabetes (T2D) account for the majority of the burden of noncommunicable disease caused by low physical activity (LPA). In order to inform future interventions, this study aims to assess the burden and trends in mortality and disability-adjusted life years (DALYs) of CVD and T2D attributable to LPA by year, location, sex, and age from 1990 to 2019. Methods Mortality, DALYs, and their age-standardised rates (ASMR, ASDR) for CVD and T2D attributable to LPA were retrieved from Global Burden of Disease (GBD) 2019. The estimated annual percentage changes (EAPCs) were calculated using linear regression model to describe the trend over time. Results From 1990 to 2019, the number of deaths caused by both CVD and T2D due to LPA increased significantly globally. However, the overall ASMR and ASDR for CVD declined over this same period [EAPC for ASMR (CVD) = −1.44 (95% CI: −1.50–1.38), EAPC for ASDR (CVD) = −1.30 (95% CI: −1.35 to −1.25)]. In terms of disparities, ASMR (CVD) and ASDR (CVD) in North Africa and the Middle East were consistently higher than the global average; also, the sex difference in ASMR was greatest in Central Asia. ASMR among people aged 25–44 in high Socio-Demographic Index (SDI) region has increased significantly over the past three decades. ASMR (T2D) due to LPA showed an increasing trend year by year, with EAPC = 0.26 (95% CI: 0.13–0.39), and this rate increased faster in males than in females. Consistent with cardiovascular diseases, ASMR of type 2 diabetes attributable to LPA increased among people aged 25–44, while decreased in other age groups in high SDI region. Conclusion Interventions targeting LPA are warranted in controlling the burden of cardiovascular diseases and type 2 diabetes. Countries should adapt strategies to their local contexts, considering the sex and age differences among their populations. The 25–44 age group should be given special attention to prevent the disease burden from worsening among younger people.